O9: DETECTION OF RELEVANT GENE MUTATIONS IN GLIOMA USING PLASMA CELL FREE DNA. (27th April 2021) - Ita, M; Nolan, Y; Toulouse, A; Wang, JH; Lim, CH; O'sullivan, MGJ; Kaar, GF; Redmond, HP
Abstract: Background: Comprehensive molecular profiling of gliomas provide information essential for accurate biological classification beyond traditional histopathology. Genomic profiling utilizing tumour tissue samples inevitably involves obtaining tissues through potentially hazardous surgical procedures or stereotactic biopsies carrying risks of morbidity and mortality. Tissues from biopsies may also be insufficient or fail to capture a comprehensive picture of the tumours genetic profile due to tumour heterogeneity. In these contexts, complementary minimally invasive strategies are needed for molecular profiling of gliomas. Cell free DNA (cfDNA) has emerged as an easily accessible biomarker containing fragments of circulating tumour DNA (ctDNA) released into plasma through apoptosis. We explored its potential utility in genomic profiling of brain tumours. Method: Plasma cfDNA from patients with radiographically suspected brain malignancies were extracted and quantified before planned surgical interventions. Cell free DNA was extracted using a QIAamp Circulating Nucleic Acid Kit (Qiagen), and was quantified (ng cfDNA/mL) using a DS‐11 FX Spectrophotometer (DeNovix). Pathway focused profiling of somatic mutation status was performed using QBiomarker Somatic Mutation PCR Arrays for human brain cancers (Qiagen) through real time PCR (Roche). Result: Somatic mutations in human brain cancer were evaluated in the following genes; BRAF, CTNNB1/beta‐catenin, EGFR, IDH1, IDH2, KRAS, NF2, NRAS, PIK3CA, and PTEN. A total of 14 (70%) patients had greater than 1 somatic mutation detected in their plasma cfDNA. Conclusion: We postulate that glioma derived circulating tumour DNA occur in plasma, and genomic analysis using cell free DNA may complement current methods of glioma genomic characterisation. Take‐home message: Glioma derived circulating tumour DNA occur in plasma.